Implementasi Model Contextual Teaching And Learning (CTL) Dalam Pembelajaran Fiqih Pengurusan Jenazah Di SMK Negeri 3 Lubuklinggau - Ertati Ertati; Supriadi; Erlinda Wati (Edification Journal : Pendidikan Agama Islam, 2026)
This study aims to describe the implementation of the Contextual Teaching and Learning (CTL) model through the involvement of community figures in teaching the fiqh of funeral management at SMK Negeri 3 Lubuklinggau. The background of this research is based on the need to transform conventional teaching methods into a more applicable approach for vocational high school students. This study employed a qualitative approach with a case study design. Data were collected through participant observation, in-depth interviews with Islamic Religious Education (IRE) teachers, and documentation of learning outcomes. The findings reveal that the implementation of the CTL model was carried out through systematic integration between classroom theoretical reinforcement and the direct involvement of community figures as primary practitioners. This process successfully transformed learning from a theoretical approach into an authentic and meaningful learning experience. The involvement of social actors in the instructional process proved capable of optimizing cognitive understanding, sharpening psychomotor skills, and validating students' mental readiness and self-confidence in performing fardhu kifayah obligations. This study concludes that the synchronization between the school curriculum and the practical wisdom of community figures creates an adaptive learning ecosystem for vocational students in fulfilling their religious social responsibilities.